2022
DOI: 10.1093/plphys/kiac244
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of arginine and ornithine levels paces the progression of leaf senescence

Abstract: Leaf senescence can be induced by stress or aging, sometimes in a synergistic manner. It is generally acknowledged that the ability to withstand senescence-inducing conditions can provide plants with stress resilience. Although the signaling and transcriptional networks responsible for a delayed senescence phenotype, often referred to as a functional stay-green trait, have been actively investigated, very little is known about the subsequent metabolic adjustments conferring this aptitude to survival. First, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…As polyamines are crucial repressors of ethylene production in plants, higher polyamine levels resulted in lower ethylene concentrations . Notably, SeNPs play a vital role in many other abiotic and biochemical reactions in plants.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As polyamines are crucial repressors of ethylene production in plants, higher polyamine levels resulted in lower ethylene concentrations . Notably, SeNPs play a vital role in many other abiotic and biochemical reactions in plants.…”
Section: Results and Discussionmentioning
confidence: 99%
“…40 SAM was reported to be capable of forming polyamines and ethylene through the action of S-adenosylmethionine decarboxylase (SAMDC) and acetyl-CoA synthetase (ACS) enzymes, respectively. 41 We found that SeNPs treatment upregulated the activities of SAM and SAMDC in the shoots and roots and downregulated the activities of ACS and 1aminocyclopropane-1-carboxylic acid oxidase (ACO) (Figure 5A−D). Furthermore, under Cd stress conditions, SeNPstreated plants had higher concentrations of putrescine, spermidine, and spermine than those of the control, and the SeNPs-treated seedlings exhibited reduced ethylene production (Figure 5E−H).…”
Section: Senps Alter the Concentrations Of Glycine- Serine- And Sulfu...mentioning
confidence: 96%
“…As OAT uses ornithine, which comes from arginine degradation by arginase, we could hypothesize that OAT affects nitrogen remobilization during DIS by this pathway. Recently, Liebsch et al (2022) found that metabolism of basic amino acids such as arginine and ornithine is paramount in adjusting senescence progression in Arabidopsis . These two amino acids were proposed to act as respiratory substrates via P5C and glutamate but not proline, or as precursors for polyamines biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic shift in the amino acid pool prolongs the lifespan of leaves by facilitating respiratory substrates and enhancing polyamines biosynthesis. This, in turn, retards leaf senescence by interfering with the ethylene signaling pathway [ 36 ].…”
Section: Photoreceptor-mediated Leaf Senescence Under Shade Conditionsmentioning
confidence: 99%